Multicenter patch testing with a resol resin based on phenol and formaldehyde within the International Contact Dermatitis Research Group - Isaksson, Marléne; Diepgen, Thomas L. (Dermatitis, 2015)
Contact allergy to phenol-formaldehyde resins (PFRs) based on phenol and formaldehyde is not detected by a p-tertiary-butylphenol-formaldehyde resin included in most baseline patch test series. - Objective - The aims of this study were to investigate the contact allergy rate to PFR-2 in an international population and to investigate associated simultaneous allergic reactions. - Methods - Thirteen centers representing the International Contact Dermatitis Research Group included PFR-2 into their patch test baseline series during a period of 6 months in 2012. - Results - Of 2259 patients tested, 28 (1.2%) reacted to PFR-2. Of those 28 individuals, one had a positive reaction to formaldehyde and 2 to p-tertiary-butylphenol-formaldehyde resin. Simultaneous allergic reactions were noted to colophonium in 3, to Myroxylon pereirae in 5, and to fragrance mix I in 8. - Conclusions - The contact allergy frequency in the tested population (1.2%) merits its inclusion into the international baseline series and possibly also into other baseline series after appropriate investigations. Significantly, overrepresented simultaneous allergic reactions were noted for M. pereirae and fragrance mix I.